The Relationship between information literacy, learning space and TPACK on prospective teachers' digital mathematics Literacy - Yuliardi, Ricki; Kusumah, Yaya S; Nurjanah, Nurjanah; Juandi, Dadang; Said Husain, Sharifah Kartini (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2024)
This study aims to examine the relationship between information literacy, optimized learning spaces, and TPACK Skills on the mathematical digital literacy skills of prospective mathematics teachers. The method is non-experimental research with a causal correlation design and a quantitative approach using the Structural Equation Modeling (SEM) analysis method. The population in this study were undergraduate mathematics teacher candidates. The sample was obtained from as many as 216 respondents using purposive sampling from public and private universities in Riau, West Sumatra, Bengkulu, Banten, Jakarta, West Java, Yogyakarta, and East Java. The instrument used is a Likert scale on a scale of 1-5, which consists of 24 indicators representing 4 variables. Based on the results of the assumption test, validity test, and model fit test, it can be concluded that the SEM model in this study is suitable and feasible and can describe the theory and findings in the field. Based on the inner model test, it can be concluded that information literacy (LT), Optimize Learning Spaces (LS), and TPACK Skills (TK) have significant effects on mathematical digital literacy (DL) in terms of estimates and P <0.05. The results of this research indicate that the increasing need for the application of learning technology, especially in mathematics learning, requires increasing the competence of teachers and students in integrating technology in mathematics learning and digital mathematics literacy needs to be the focus of further research.